Феномен фронтиру у соціокультурному контексті - Іванова, С.В. (Археологія і давня історія України, 2021)
У статті йдеться про можливість інтерпретації археологічного матеріалу в аспекті теорії
фронтиру та його виміру у соціокультурному контексті. Висвітлено історіографію питання, можливість реконструкції міжкультурних відносин в умовах фронтиру. Проаналізовано Південно-Західний і Балкано-Карпатський фронтири, розглянуто
основні культури фронтирних зон пізнього енеоліту — доби ранньої бронзи. Окрему увагу приділено
ямній культурно-історичній спільноті, особливо її
західному ареалу, пов’язаному з буджацькою культурою. Vitalij V. Otroschenko made a great contribution
to the study of Copper and Bronze Age cultures in
Ukraine. His researches of absolute and relative chronology,
cultural changes and cultural coexistence have
particular interest in the context of this article. They
allow a reader to focus more reasonably on cultural and
historical processes of North-Western Black Sea and
Balkan-Carpathian regions staying within the frame
of the frontier theory.
Most of researchers on the topic consider the «frontier
» as a special zone of interference of different cultures.
The frontier is also meant a special area where
several cultures meet, shaping new socio-cultural relations.
The frontier differs from deeper territory in
higher mobility, where movement of large groups of
people create new forms of cultural and social contacts.
The system of intercultural communication depends on
many factors, including the history of formation of the
cultural landscape of the territory where intercultural
communication is taking place.
Originally, the concept of «frontier» was applied
exclusively to American history, but now we meet it
in works related to the history of Ukraine. The situation
of the frontier zone has begun to attract archeologists
though in a rather narrow area concerning social
changes (in the context of anthropological archeology).
The special nature of the source base of history
and archaeology, especially in the preliterate period,
determines similarities and differences of frontier
problems studying by these sciences. The specificity
of archaeological artefacts, on which the study of archaeological
cultures relies to a large extent, must also
be taken into account: they can spread over quite long
distances in the means of exchange, without people
movement.
In archaeological research of European Bronze Age,
the Pit Grave (Yamnaya) culture is in the great importance;
interest towards it has been reinforced by the
latest genetic research. The mobility of society, innovation
in the material culture of its western range allowed
us to consider the Pit Grave cultural and historical
community within the frontier theory.
At the same time, the comparison of two adjacent
frontier zones (North-Western Black Sea Coast and
Balkan-Carpathian area) made it possible to compare
their common and special traits, in the context of their
interconnection and mutual influences, taking into account
the aspect of social identification.